The spiral staircase : my climb out of darkness - Armstrong, Karen, 1944- (New York : Anchor Books, 2005)
The author relates her decision to leave her convent after failing to find religious fulfillment, her struggles with depression and epilepsy, her realization of her calling, and her career working with sacred texts.
T. S. Eliot, Ash-Wednesday, I xxi -- 1 Ash Wednesday 3 -- 2 The Devil of the Stairs 46 -- 3 I Renounce the Blessed Face 78 -- 4 Consequently I Rejoice 120 -- 5 Desiring This Man's Gift and That Man's Scope 159 -- 6 The Usual Reign 192 -- 7 Infirm Glory 224 -- 8 To Turn Again 264.
Originally published: New York : A. A. Knopf, 2004.
Keywords: Armstrong, Karen, -- 1944-; Ex-nuns -- Biography